The Legal Status of Members of a Legal Entity in Bankruptcy Proceedings - Tamošiūnienė, Egidija; Višinskis, Vigintas; Balsiukienė, Audronė; Kirkutis, Mykolas (Teisė, 2022)
This article examines the problems of the legal status of members of a legal entity in bankruptcy proceedings. The article discusses the interest of member of a legal entity in the bankruptcy proceedings and what circumstances justify their participation in this process. The rights and obligations of members of a legal person at the stage of initiation and execution of bankruptcy proceedings are also examined. It analyzes the actions that can be taken by members of a legal entity in order to restore the solvency of the legal entity and terminate bankruptcy proceedings. The article also analyzes the problems of the position of an individual company owner in the bankruptcy proceedings of an individual company.
Keywords: bankruptcy; member of a legal entity; unlimited liability company